O16 Use of online assessment tools by risk taking men. (23rd May 2012) - Ward, P; Power, L; Nardone, A; Hartney, T; Delpech, V
Abstract : Background: Condom use by gay men has slipped since the 1990s. In late 2011 THT (as part of CHAPS) launched a condom campaign for younger men, promoting a web-based HIV risk assessment tool. Methods: The Clever Dick/Smart Arse campaign encouraged use of an online risk assessment tool with prize incentives. This gave an instant rating on sexual activity in the past year, with a detailed risk report on request. This covered behaviours affecting HIV risk including PEP, poppers, condoms, HIV disclosure, receptive or insertive modality, monogamy, treatment and viral load. Results: 7240 risk assessments were undertaken in 10 weeks of whom 1810 requested their full risk assessment ("Sexscore") and agreed to further contact. There were 101 248 page views by over 17 000 unique website visitors with average visit time of 3.03 min. Preliminary analysis of 4574 respondents shows high levels of risky behaviours. The majority were not in regular clinic contact while a third had never had a sexual health screen. 24% had never tested for HIV while 10% were knowingly HIV+ (of whom 62% had undetectable VL throughout the year). Over half (56%) had five or more sexual partners in the year. 53% of HIV+ men and 51% of other men reported UAI with one or more partners and 59% of all participants discussed serostatus before sex. Conclusion: Gay men will engage about risk taking if feedback is instant and anonymous, including those never in contact with sexual health services. Men reporting risk behaviours can be targeted for subsequent interventions.